Seasonal patterns of burrow architecture and morphological adaptations to digging in three sympatric species of South African mole-rat, Bathyergus suillus (Shreber, 1782), Georychus capensis (Pallas, 1778) and Cryptomys hottentotus hottentotus (Lesson, 1826) - Bennett, Nigel Charles (University of Pretoria, 2013)
Thesis (PhD)--University of Pretoria, 2013.